Parents' attitudes toward children's vaccination as a marker of trust in health systems. Issue 11 (2nd November 2021) - Tal, Orna; Ne'eman, Yifat; Sadia, Rotem; Shmuel, Rouchama; Schejter, Eitan; Bitan, Michal
ABSTRACT: Children's vaccination is a major goal in health-care systems worldwide; nevertheless, disparities in vaccination coverage expose socio-demographic accessibility gaps, unawareness, physicians' disapproval and parents' incomplete adherence reflecting insufficient public-provider trust. Our goal was to analyze parents' attitude toward children's vaccination in correlation with trust among stakeholders. A total of 1031 parents replied to a "snowball" questionnaire; 72% reported high trust in their physician, 42% trusted the authorities, 11% trusted internet groups. Among minorities, parents who fully vaccinate their children were younger, live in urban areas, eat all kinds of foods and trust the authorities, similar to the general population. Low adherence to children's vaccination was correlated with trusting internet groups. Females complied significantly more to child vaccination, although in our study mothers were more highly educated and trusted authorities more than males. The results enable to draw a profile of the "vaccination compliant parent" (with an academic degree, young, urban, eats all kinds of foods, uses conservative medicine). Trust is a major factor influencing vaccination, yet external forces such as community voices, social trends and opinions of religious leaders may play a role in vaccination adherence, beyond personal beliefs, individual habits and self-care. In Israel, education and "healthy behavior" perception alongside generous coverage encourage most parents to comply with the routine vaccination program. In the shade of pandemic outbreaks, we suggest a social-determinant transparent approach to encourage parents to vaccinate their children. Social and religious leaders can pose as agents of change, especially in the case of less educated parents.